Job related risks in agriculture workers from Latin America: a systematic review - Matabanchoy-Salazar, Johana Madelyn; Díaz-Bambula, Fátima (Universidad y Salud, 2021)
Introduction: International Labour Organization (ILO) guidelines promote inter-sectorial alliances in areas such as health and safety in agricultural sector jobs. Objective: To identify labor risks and their health consequences in Latin American workers by means of a systematic review covering the 2010 – 2020 period. Materials and methods: A search in the Scielo, EBSCO, and LILACS databases was conducted using the PRISMA-P guide. The keywords used were: “salud”, “agrícola”, and “agricultura” in Spanish; “health”, “agriculture”, and “agricultural” in English; and “saúde” and “agrícola” in Portuguese. Proper definitions of inclusion and exclusion criteria were included. Results: a total of 65 articles were retrieved, identifying the prevalence of several occupational risks (OR) such as chemical risks and ergonomic and biological risks (animal contact), which were classified as the first and second most prevalent risks, respectively. Brazil and Colombia have the largest number of publications in reference to this topic. Conclusions: An understanding of the rural context in relation to the labor risks was accomplished. Likewise, the importance of the comprehension of health determinants from a structural point of view is highlighted, which have become challenges in promoting public health care.